Efikasi Bakteri Entomopatogen Bacillus thuringiensis Barliner sebagai Agens Hayati Spodoptera litura Fabricus pada Lahan Pasang Surut dan Rawa Lebak - Arsi Arsi; Yulia Pujiastuti; Siti Herlinda; Suparman SHK; Bambang Gunawan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Arsi A, PujiastutiY, HerlindaS, SHK Suparman, Gunawan B. 2019. Efficacy of entomopathogenic bacteria bacillus thuringiensis barliner as biocontrol agent against spodoptera litura fabricus in tidal and swampy areas In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 254-263. Palembang: Unsri Press. The entomopathogenic bacteria, B. thuringiensis is used as an insect control agent for Spodoptera litura pests in food plants and horticultural plants. This research was conducted to figure out the toxicity of entomopathogenic bacteria B. thuringiensis to S.litura inhabiting tidal and swampy areas. The entomopathogenic bacteria B. thuringiensis was derived from tidal and swampy areas. Isolation, and identification of the bacteria were conducted in the Laboratrory of Phytopathology and the Laboratory of Entomology, Department of Plsnt Pest and Disease, Faculty of Agriculture, Sriwijaya University Indralaya, under laboratory conditions under temperature of 26o C and relative humidity of 79.6%. the results showed that S. litura larvae treated topically with sopres of B. thuringiensis at spore density of 1 x 106sel/mL was varied. The highest larval mortality was foun in PUM isolaste amounted to 100% with LT50 amounted to 0.56 day, while the lowest mortality was found in PIM isolate amounted to 73.3% with LT50 reached 5.46 days.Keywords: lethal time 50, mortality, tested insect